Perylene Diimide‐Based Conjugated Polymers for All‐Polymer Solar Cells. Issue 55 (11th August 2020) - Shi, Qinqin; Wu, Jianfei; Wu, Xiaoxi; Peng, Aidong; Huang, Hui
Abstract: In recent decades, non‐fullerene acceptors (NFAs) are undergoing rapid development and emerging as a hot area in the field of organic solar cells. Among the high‐performance non‐fullerene acceptors, aromatic diimide‐based electron acceptors remain to be highly promising systems. This review discusses the important progress of perylene diimide (PDI)‐based polymers as non‐fullerene acceptors in all‐polymer solar cells (all‐PSCs) since 2014. The relationship between structure and property, matching aspects between donors and acceptors, and device fabrications are unveiled from a synthetic chemist perspective. Abstract : Let the sunshine in : Important progress of perylene diimide (PDI)‐based polymers as non‐fullerene acceptors in all‐polymer solar cells (all‐PSCs) is reviewed with focus on relationship between structure and property, matching aspects between donors and acceptors, and device fabrications.